Investigation of equilibrium CO2 solubility in 35 wt% aqueous 1-(2-aminoethyl) piperazine (AEP) and performance study over monoethanolamine for CO2 absorption. (2022) - Dey, Anirban; Saini, Bharti; Balchandani, Sweta C.; Kumar Dash, Sukanta
Abstract: The present study investigates the CO2 absorption capacity of 1-2-(aminoethyl)piperazine (AEP) as a potential solvent for post combustion CO2 capture. The CO2 absorption performance has been evaluated in terms of Equilibrium CO2 solubility at varied temperature and pressure range. The CO2 solubility measurement was conducted using high pressure stirred autoclave reactor within the temperature and Pressure range of (308.15–328.15) and (2–200) kPa respectively. The equilibrium CO2 solubility data are further correlated using semi-empirical model and equilibrium based Modified Kent-Eisenberg model which shows a better agreement with the generated experimental data. In addition to this, a comprehensive parametric study was also carried out in Aspen-Plus Platform to evaluate the performance of proposed solvent over conventional solvent monoethanolamine (MEA). Influence of various important operating parameters such as flow rates of solvent and Gas medium, amine concentration, solvent inlet temperature and (L/G) ratio on the % CO2 removal was studied.